Constructing the EU's Political Identity - Saurugger, Sabine; Thatcher, Mark. (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2022)
This book examines the construction of the EU's political identity (or identities), variations in its strength, and the nature of its content. Drawing on studies both on European nation-state formation and on the EU's identity, the chapters take a top-down approach and analyse how EU institutions in different major policy domains have themselves sought to create political identity through policy making. The authors define the construction of EU political identity and set out empirically applicable indicators to assess political identity in policy making. They analyse the construction of identity through a process-oriented approach that explicitly includes contestation and the existence of rival political identities. Comparing across policy domains, the contributions suggest that the ability of EU institutions to construct an EU political identity has been limited not only by existing national identities but also by the coexistence of rival EU political identities within policy domains. Hence, it has been difficult for EU institutions to establish a strong identity, with identity being strongest where there are clear external alternatives and limited rival identities within the EU. Sabine Saurugger is Professor of Political Science at Sciences Po Grenoble, France, and Research Fellow at the Institut Universitaire de France. Mark Thatcher is Professor of Political Science at Luiss University Rome, Italy, and Visiting Professor at LSE, UK.
1. Constructing EU's Political Identity in Policy Making (Sabine Saurugger & Mark Thatcher) -- 2. Constructing and De-constructing the European Political Identity: The Contradictory Logic of the EU's Institutional System (Sergio Fabbrini) -- 3. Affirming Europe with Trade: Deal Negotiations and the Making of a Political Identity (Francesco Duina & Ezekiel Smith) -- 4. Transforming Identity in International Society: The Potential and Failure of European Integration (Thomas Diez) -- 5. Do Central Bankers Dream of Political Union? From Epistemic Community to Common Identity (Erik Jones) -- 6. The EU's Legal Identities and the Court of Justice of the EU (Sabine Saurugger & Fabien Terpan) -- 7. Common Market, Normative Power or Super-State? Conflicting Political Identities in EU Asylum and Immigration Policy (Sandra Lavenex) -- 8. Direct and Market Governance Paths for the Creation of an EU Political Identity: Cultural Heritage Policy (Mark Thatcher) -- 9. Understanding the Identity of a Policy Field: The European Commission and Liberal Modernization in the Doman of Labour and Social Policy (Georg Menz) -- 10. Comment: The EU and European Identity (Neil Fligstein) -- 11. EU Political Identity, Integration and Top-down Analysis: A Reply to Neil Fligstein (Sabine Saurugger & Mark Thatcher).
Keywords: Europe-Politics and government; Comparative government; Political sociology; Identity politics; European Politics; Comparative Politics; Political Sociology; Identity Politics